Free "Cook Book" for gridding bathymetric data. (26th February 2013) - Kumar, Mohi
Abstract : The International Hydrographic Organization (IHO) and the General Bathymetric Chart of the Oceans (GEBCO) program of the United Nations Educational, Scientific and Cultural Organization's Intergovernmental Oceanographic Commission (UNESCO IOC) have created a free manual to help users prepare quality bathymetric grids from available data points. The new "IHO‐IOC GEBCO Cook Book, " released last year and available at http://www.gebco.net, provides step‐by‐step instructions, screenshots, command lines, and snippets of code applied on actual data, to guide users through the process of gridding data.